Anforderungen an die Neurorehabilitation nach epilepsiechirurgischen Eingriffen im linken Temporallappen bei Patienten mit neurokognitivem Risikoprofil - Schwarz, Michael; Badstübner, Annabell Sophie; Meyn, Karlotta; Walther, Katrin; Hamer, Hajo (Fortschritte der Neurologie - Psychiatrie, 2023)
Introduction In case of pharmacoresistant focal epilepsy, surgery is often the only way to achieve seizure freedom. These operations may result in cognitive deficits, especially with surgery in the left temporal lobe. The aim of this study was to determine whether patients operated in the left or right tem-poral lobe, respectively, have different cognitive outcomes. Furthermore, it was investigated if there was a positive influence of occupational therapy on neurorehabilitation in epilepsy patients. Methods In all patients cognitive performance was assessed preoperatively and six months postoperatively. Patient groups with surgery in the right and left temporal lobe were compared. Additionally, single cases of patients who had undergone extensive pre- and postoperative occupational therapy were analyzed. Results There was a significantly better cognitive outcome in patients who underwent surgery in their right temporal lobe. Occupational therapy was highly beneficial in patients after left temporal lobe surgery. Conclusion Occupational therapy after left temporal lobe surgery is adapted to find individual solutions for the patient s problems and to implement effective cognitive training strategies.
CRIS-Team Scopus Importer:2024-12-16
Keywords: Epilepsie; Epilepsiechirurgie; Ergotherapie; Neuropsychologie; Temporallappen